Dielectric layers suitable for high voltage integrated trench capacitors - vom Dorp, Joachim; Erlbacher, Tobias; Bauer, A. J.; Ryssel, Heiner; Frey, Lothar (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2011)

Improving module performance and reliability in power electronic applications by monolithic integration of RC-snubbers - Erlbacher, Tobias; Schwarzmann, Holger; Bauer, A. J.; Berberich, S. E.; vom Dorp, Joachim; Frey, Lothar (24th International Symposium on Power Semiconductor Devices and ICs, ISPSD'12, 2012)
Monolithic integration of RC snubbers in power electronic applications offers great opportunities. The presented devices provide tight tolerances and enable high integration densities. Especially, the incorporation into power modules enables reduction of electromagnetic interferences in accordance with reliable lifetime predictions. © 2012 IEEE.
Keywords: dielectric reliability; monolithic integration; power module; RC-snubber

Monolithic RC-snubber for power electronic applications - vom Dorp, Joachim; Berberich, S. E.; Erlbacher, Tobias; Bauer, Anton; Ryssel, Heiner; Frey, Lothar (2011 IEEE 9th International Conference on Power Electronics and Drive Systems, PEDS 2011, 2011)